A Review of CRP as a Biomarker of COVID-19 (Delta Medical College Journal, 2022)
The outbreak of coronavirus disease 2019 (COVID_19) is an emerging global health threat. The healthcare workers are facing challenges in reducing the severity and mortality across the world. Patients with severe form of COVID_19 are generally treated in the intensive care unit, while mild or non_severe patients are treated in the isolation ward or at home. It is important to identify early and give treatment to reduce the disease severity and improve the outcomes. There is no credible and convenient biomarker to predict the severity of the disease. Therefore, the exploration of biomarkers is deemed necessary. We aimed to review the diagnostic and early prognostic value of C-reactive protein (CRP) in COVID-19 patients. In a number of studies, CRP showed different distribution feature and differences existed in various ages, clinical types and outcomes of COVID-19 patients. The present study reviews the role of CRP level as a marker in indicating the severity of patients with COVID_19.Delta Med Col J. Jul 2020 8(1): 41-45